2015
DOI: 10.1074/jbc.m114.576520
|View full text |Cite
|
Sign up to set email alerts
|

A Globin Domain in a Neuronal Transmembrane Receptor of Caenorhabditis elegans and Ascaris suum

Abstract: Background: GLB-33 is a putative neuropeptide receptor in C. elegans with a globin domain. Results: Recombinant globin domain displays a ferric hydroxide-ligated form. When reduced, it can bind CO or O 2 and reduce nitrite to NO. Conclusion:The globin domain may serve as an oxygen sensor or nitrite reductase. Significance: Oxygen-sensing mechanisms are relevant for neuropeptide receptor binding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…These components have g values similar to those of OH – adducts of other heme proteins, such as cytochrome c peroxidase, 45 human hemoglobin, 46 horse heart myoglobin, 46 and Caenorhabditis elegans globin-33. 47 Nicoletti et al showed that at high pH hemoglobin from Thermobifida fusca forms two hydroxo complexes with different sets of g values, 48 which they explained with the OH – group being hydrogen-bonded to different extents to nearby residues. In the case of hemoglobin, the component with broader features was assigned to a strong His/OH – coordination.…”
Section: Discussionmentioning
confidence: 99%
“…These components have g values similar to those of OH – adducts of other heme proteins, such as cytochrome c peroxidase, 45 human hemoglobin, 46 horse heart myoglobin, 46 and Caenorhabditis elegans globin-33. 47 Nicoletti et al showed that at high pH hemoglobin from Thermobifida fusca forms two hydroxo complexes with different sets of g values, 48 which they explained with the OH – group being hydrogen-bonded to different extents to nearby residues. In the case of hemoglobin, the component with broader features was assigned to a strong His/OH – coordination.…”
Section: Discussionmentioning
confidence: 99%
“…Addition of dithionite to as-purified Gs GCS leads to the ferrous deoxy form with absorption maxima at 427, 561, and 532 nm, typical of LS ferrous Gbs in which the heme iron is ligated to two histidines (so-called hexa-coordination), e.g. neuroglobin [49] , cytoglobin [50] , Ce GLB6 [51] , Ce GLB26 [52] , and Ce GLB33 [24] . Of note, the Q-bands of the ferrous deoxy form appear less sharp than expected for hexa-coordination, indicating a fraction of penta-coordination which might facilitate the binding of gaseous ligands, as has been shown in vitro for Gs GCS 162 [16] .…”
Section: Resultsmentioning
confidence: 99%
“…The cDNA of Gs GCS (codons 1–300, NCBI reference protein sequence WP_010943923) was amplified by PCR using 5′-CCGCTCGAGATGCTGACCATGCAGGAAATAAAGG-3′ and 5′- GGGTACCCTAGTGGGGAGTGTAGG-3′ as forward and reverse primer, respectively. The reaction conditions applied for PCR are described elsewhere [24] . The construct was cloned into a pBAD-a vector using XhoI and HindIII restriction sites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the g -tensor of species OH1′ is very similar to the one found for horseradish peroxidase (HRP) [ 30 ], the parameters of OH2/OH2′ and OH3′ are more common for alkaline forms of cytochrome c peroxidase and mammalian myoglobin [ 24 , 29 , 31 ]. A high diversity of hydroxo-ligated species was found in hemoglobin of Thermobifida fusca [ 32 ] and the globin domain of the GLB-33 globin of C. elegans [ 33 ]. The Arg-232 variants (both single and double variant) do not exhibit hydroxo-ligated species.…”
Section: Resultsmentioning
confidence: 99%